Dispersive waves and caustics - Arthur D. Gorman (International Journal of Mathematics and Mathematical Sciences)
The Lagrange manifold (WKB) formalism enables the determination of the asymptotic series solution of linear, non-dispersive wave equations at turning points. The formalism is adapted to include those equations which model dispersive waves.